Burying beetles regulate the microbiome of carcasses and use it to transmit a core microbiota to their offspring. Issue 8 (8th September 2017) - Shukla, Shantanu P.; Vogel, Heiko; Heckel, David G.; Vilcinskas, Andreas; Kaltenpoth, Martin
Abstract: Necrophagous beetles utilize carrion, a highly nutritious resource that is susceptible to intense microbial competition, by treating it with antimicrobial anal and oral secretions. However, how this regulates the carcass microbiota remains unclear. Here, we show that carcasses prepared by the burying beetle Nicrophorus vespilloides undergo significant changes in their microbial communities subsequent to their burial and "preparation." Prepared carcasses hosted a microbial community that was more similar to that of beetles' anal and oral secretions than to the native carcass community or the surrounding soil, indicating that the beetles regulated the carcass microbiota. A core microbial community (Xanthomonadaceae, Enterococcaceae, Enterobacteriaceae and Yarrowia yeasts) was transmitted by the beetles to the larvae via the anal and oral secretions and the carcass surface. These core taxa proliferated on the carcass, indicating a growth conducive environment for these microbes when associated with beetles. However, total bacterial loads were higher on decomposing carcasses without beetles than on beetle‐prepared carcasses, indicating that the beetles and/or their associated symbionts suppress the growth of competing microbes. Thus, apart from being a nutritional resource, the carcass provides a medium for vertical transmission of a tightly regulated symbiotic microbiota, whose activity on the carcass and in the larval gut may involve carcass preservation as well as digestion.